2020
DOI: 10.1001/jamanetworkopen.2020.11768
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Machine Learning Model for Survival Risk Stratification of Patients With Advanced Oral Cancer

Abstract: Key Points Question Can a machine learning model provide survival risk stratification for patients with advanced oral cancer who have comprehensive clinicopathologic and genetic data? Findings In this 15-year cohort study of 334 patients, a risk stratification model using comprehensive clinicopathologic and genetic data accurately differentiated the high-risk group from the low-risk group in postoperative cancer-specific and locoregional recurrence–free sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 43 publications
0
42
0
Order By: Relevance
“…In this study, we propose a novel machine learning (ML)-based predictive model called iPMI for the practical identification of PMI in women with early-stage cervical cancer who are candidates for primary radical surgery. This category of modeling technique is increasingly employed in cancer prognostic model development studies with highly reliable predictive performance [21][22][23]. To validate the effectiveness and robustness of the iPMI model developed by using the random forest (RF) method, we compared its predictive performance with those of conventional logistic regression (LR) and other widely used ML classifiers including decision tree (DT), k-nearest neighbor (kNN), multi-layer perceptron (MLP), naive Bayes (NB), support vector machine (SVM), and extreme gradient boosting (XGB).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we propose a novel machine learning (ML)-based predictive model called iPMI for the practical identification of PMI in women with early-stage cervical cancer who are candidates for primary radical surgery. This category of modeling technique is increasingly employed in cancer prognostic model development studies with highly reliable predictive performance [21][22][23]. To validate the effectiveness and robustness of the iPMI model developed by using the random forest (RF) method, we compared its predictive performance with those of conventional logistic regression (LR) and other widely used ML classifiers including decision tree (DT), k-nearest neighbor (kNN), multi-layer perceptron (MLP), naive Bayes (NB), support vector machine (SVM), and extreme gradient boosting (XGB).…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning (ML) models may also be used to identify prognostic factors. Tseng et al [ 59 ] incorporated clinical, pathological and cancer-related gene features of patients with advanced oral cancer and found that only 6 of 44 genes analyzed are necessary for further prognostic risk stratification. Therefore, costs and resources for molecular analysis could be reduced with targeted requests.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple ML models that risk-stratify patients with a disease or prepare patients for surgery have been recently developed and validated (16,(20)(21)(22)(23)(24)(25). These ML models have been shown to better predict mortality than conventional logistic regression after liver cancer surgery, aortic aneurysm surgery, and cardiac surgery.…”
Section: Risk Stratificationmentioning
confidence: 99%